Formulasi dan Evaluasi Sediaan Lotion Ekstrak Daun Kembang Sepatu Merah (Hibiscus rosa-sinensis L.) sebagai Antioksidan - Mia Arifka; Budi Setiawan; Selvia Susanti (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2024)
Red hibiscus leaves (Hibiscus rosa sinensis L.) are used as medicinal plants because they contain alkaloids, glycosides, flavonoids, phenols and saponins. Previous studies have formulated liquid detergent and creambath preparations from hibiscus leaf extract. This study was experimental using the maceration method with 96% ethanol solvent for 5 days and was shaken every 1x24 hours. Red hibiscus leaf extract was extracted using 96% ethanol solvent and then formulated into lotions with various different concentrations: F0 did not contain extract, F1 contained 2.5% extract, F2 contained 5% extract, and F3 contained 7.5% extract. Evaluation of the preparations was carried out through organoleptic tests, homogeneity, pH, spreadability, and skin irritation. The results of the physical evaluation showed that the lotion with red hibiscus leaf extract had a green to dark green color, a semi-solid or cream texture, pH 6, and the spreadability obtained ranged from 6.2 cm to 7 cm. Irritation tests conducted by several panelists showed that the lotion preparation was safe to use. From the research that has been conducted, it can be concluded that red hibiscus leaf extract (Hibiscus rosa sinensis L.) can be formulated into a lotion preparation.